2018
DOI: 10.1159/000486683
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics, Early Adversity and Child and Adolescent Mental Health

Abstract: Epigenetic modification, such as DNA methylation (DNAm), is a mechanism that can help explain how early adversities can engender long-term vulnerability for mental health problems. At present, there is preliminary evidence to support the possibility of epigenetic mediation: environmental factors are reported to influence offspring DNAm, which in turn associate with child and adolescent psychopathology. However, all analyses have been correlational in nature and, as these studies have focussed on children and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…This transmission suggests that behavior is not only learned through one's personal experiences but also through the experiences of ancestors. Epigenetic modification, including DNA methylation is a mechanism that can help explain how early adversities increase risk for mental health problems (Barker, 2018).…”
Section: Genetic and Epigenetic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This transmission suggests that behavior is not only learned through one's personal experiences but also through the experiences of ancestors. Epigenetic modification, including DNA methylation is a mechanism that can help explain how early adversities increase risk for mental health problems (Barker, 2018).…”
Section: Genetic and Epigenetic Factorsmentioning
confidence: 99%
“…There is also evidence supporting epigenetic changes as a mechanism for altering gene expression that occurs with ACEs (Lang et al, 2020). Despite promising evidence, however, generalizations cannot be made about epigenetic changes because many studies have low sample size and rely on self-report of ACEs, among other methodological issues (Barker, 2018). Consequently, understanding of DNA methylation as a causal mechanism between adversity and mental health disorders is unclear (Barker, 2018).…”
Section: Acesmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigeneticallymodified loci have been linked to a wide range of mental disorders such as schizophrenia, 40 as well as childhood onset disorders such as ADHD, 41 and ASD, 42 but conflicting and non-replicated associations mean that the causal relationships remain poorly understood. 43 LifeCycle mental health studies can currently analyse DNA methylation data on 14,368 offspring cohort participants (Figure 5), measured at birth (cord or placenta blood; N=7,783), childhood (0-12 years; N=3,055), adolescence (…”
Section: Mediating Pathways -Epigeneticsmentioning
confidence: 99%
“…Life course theory proposes that early adversity has long-term effects on individuals’ physical and mental health, resulting in the individual’s physical and mental health disadvantages throughout life ( Matthias and Klaus, 2016 ; Bellis et al, 2019 ; Sieber et al, 2020 ). Some studies demonstrated that adolescents who experience early adversity tend to show more behavioral problems ( Barker, 2018 ; Wenming et al, 2020 ), and early adversity is significantly associated with depression and anxiety in middle school students ( Junmei et al, 2020 ). Compared to university students who grew up living with their parents, those who had been left behind in childhood were reported to have higher levels of mental disorders, including suicidal ideation ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%